Theory is History - Amin, Samir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book focuses on a central concept that (3z(BTheory is History(3y(B, as the theory of capitalism can only be formulated on the basis of an analysis of its history. In contrast, bourgeois thinking replaces the analysis of historical capitalism with an abstract theory without any links to reality. (3z(BEconomics(3y(B, which is the theory of an imaginary system, then becomes an apologia intended to give legitimacy to the behaviour of the owners of capital. The author pays special attention to the globalization of the law of value. The individual chapters illustrate the author$1 (Bs thesis by focusing on the links between capital and land ownership, between modernity and religious interpretation, and on questions of the global expansion of capitalism, particularly the ways it has evolved in certain countries, in this case Russia and China. This anthology supplements the author$1 (Bs previous work, centred on the rise of the South$1 (Bhis reading of capitalism focusing on its imperialist nature.s
The globalised law of value -- Capitalism and ground rent -- Modernity and interpretations of religions -- Re-reading the post war period -- Historical capitalism; accumulation by dispossession -- The two paths of historical development; the contrast between Europe and China -- Russia in the world system; geography or history? -- China, the emerging nation.
Keywords: Social sciences; Social Sciences; Political Theory; Political Economy